Regulation of SARS-CoV-2 infection by diet-modulated gut microbiota - Tieu, Vivian; Tibi, Sedra; Ling, Jun (Frontiers in Cellular and Infection Microbiology, 2023)
The SARS-CoV-2(COVID-19) coronavirus has claimed millions of lives since late 2019, yet there are still many unexplored facets of its pathogenic nature and clinical consequences. As COVID-19 affects multiple human organs and the gut microbiota influences the functions of broad organ systems, it is important to examine the immunomodulatory role of gut microbiota in COVID-19 pathogenesis, especially the gut-lung axis. Dysbiosis of the commensal intestinal microbes and their metabolites (e.g., SCFAs) as well as the expression and activity of ACE2 in the gut could influence the host’s immune system in COVID-19 patients. Moreover, it has been known that the elderly and individuals diagnosed with comorbidities (e.g., hypertension, type 2 diabetes mellitus, cardiovascular disease, etc.) are more susceptible to gut flora alterations, SARS-CoV-2 infection, and death. Thus, in this review we will focus on analyzing how the gut microbiota regulates the immune system that leads to different responses to SARS-CoV-2 infection. Since diet is a major factor to modulate the status of gut microbiota, dietary influence on COVID-19 pathogenesis will be also discussed, aiming to shed light on how diet-modulated gut microbiota regulates the susceptibility, severity, and treatment of SARS-CoV-2 infection.